Konflikty, kompromisy i rezerwuar międzykulturowości w małżeństwach mieszanych - Cukras-Stelągowska, Joanna (Kultura-Społeczeństwo-Edukacja, 2022)
In this article, I discuss the issues of mixed marriages, referring to research conducted by Polish sociologists, psychologists and educators. On this basis, I try to show possible areas of conflict in this type of relationships, various strategies for working out compromises as well as various relations with the social microstructure. I emphasise problems related to bringing up children in a bi-cultural family environment, in particular aspects of bi-religious home education. My intention is also to identify potential areas of intercultural enrichment and the emergence of new cultural capital in mixed families. I also reflect on PolishJewish marriages by recalling the biography of a representative of the third generation of the Holocaust survivors, married to a Catholic, who has introduced, together with her husband, a model of dualistic education. The research was based on the biographical method, unstructured/indepth interviews. The article presents one of the elements of broader research, which focused on the construction of the socio-cultural identity of the narrators.